2020
DOI: 10.1113/jp278888
|View full text |Cite
|
Sign up to set email alerts
|

Identification and classification of interstitial cells in the mouse renal pelvis

Abstract: Platelet-derived growth factor receptor-α (PDGFRα) is a novel biomarker along with smooth myosin heavy chain for the pacemaker cells (previously termed 'atypical' smooth muscle cells) in the murine and cynomolgus monkey pelvis-kidney junction. r PDGFRα + cells present in adventitial and urothelial layers of murine renal pelvis do not express smooth muscle myosin heavy chain (smMHC) but are in close apposition to nerve fibres. r Most c-Kit + cells in the renal pelvis are mast cells. Mast cells (CD117 + /CD45 +)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…To evaluate the expression of Ca 2+ -activated K + (SK3) and Ca 2+ -activated Cl − (ANO-1) channels, which have been previously reported in PDGFRα-positive ICs of other smooth muscle organs 12 14 , in PDGFRα-positive ICs of the smooth muscle layer of the murine vas deferens, we double immunostained for PDGFRα and SK3, and for PDGFRα and ANO-1, and found that PDGFRα-IR was not co-labeled with SK3-IR and ANO-1-IR (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the expression of Ca 2+ -activated K + (SK3) and Ca 2+ -activated Cl − (ANO-1) channels, which have been previously reported in PDGFRα-positive ICs of other smooth muscle organs 12 14 , in PDGFRα-positive ICs of the smooth muscle layer of the murine vas deferens, we double immunostained for PDGFRα and SK3, and for PDGFRα and ANO-1, and found that PDGFRα-IR was not co-labeled with SK3-IR and ANO-1-IR (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…SK3/PDGFRα-positive ICs have also been identified in the smooth muscle layers of bladder 15 and seminal vesicle 20 . In addition, the ANO1 channel is expressed in PDGFRα-positive ICs of renal pelvis where it may influence their spontaneous activities 14 . In the present study, neither SK3 nor ANO-1 channels were detected in the PDGFRα-positive ICs of the smooth muscle layer of the murine vas deferens.…”
Section: Discussionmentioning
confidence: 99%
“…The use of immunohistochemistry or the platelet‐derived growth factor receptor‐α (PDGFRα) eGFP reporter mouse strain revealed that cells at the pelvis–kidney junction (PKJ) co‐expressed PDGFRα and smooth muscle myosin heavy chain (smMHC) (Grainger et al . 2020). Such PDGFRα + /smMHC + cells were reduced in number in the distal renal pelvis, where PDGFRα − /smMHC + cells (TSMCs) formed the muscle wall.…”
mentioning
confidence: 99%
“…The molecular and pharmacological results presented agree well with previous reports of regional distribution and temporal properties of the Ca 2+ signals in ASMCs, TSMCs and two populations of ICs (Lang & Hashitani, 2019), as well as demonstrating major differences in PDGFRα + ICs and c‐Kit + ICs in expression of SK3 and Ano1 channels from PDGFRα + cells and ICC in the colon (Grainger et al . 2020). While PDGFRα + ICs in the renal pelvis express ANO1 transcripts and protein, expression of ANO1 in c‐Kit + ICs has yet to be determined.…”
mentioning
confidence: 99%
See 1 more Smart Citation